Band alignment between GaN and ZrO2 formed by atomic layer deposition - Ye, Gang (2014)
The band alignment between Ga-face GaN and atomic-layer-deposited ZrO2 was investigated using X-ray photoelectron spectroscopy (XPS). The dependence of Ga 3d and Zr 3d core-level positions on the take-off angles indicated upward band bending at GaN surface and potential gradient in ZrO2 layer. Based on angle-resolved XPS measurements combined with numerical calculations, valence band discontinuity ΔE V of 1 ± 0.2 eV and conduction band discontinuity ΔE C of 1.2 ± 0.2 eV at ZrO2/GaN interface were determined by taking GaN surface band bending and potential gradient in ZrO2 layer into account.